Anthurium gallardoae and Xanthosoma isabellanum (Araceae), two new species from coastal Ecuador - Cornejo, Xavier; Croat, Tom (Phytotaxa, 2021)
Anthurium gallardoae and Xanthosoma isabellanum, two new species of Araceae endemic to coastal Ecuador, both originally collected sterile in Manabí and Guayas provinces, respectively, and kept in cultivation until flowering at home in the city Guayaquil are here formally described and illustrated.